Mosquit Mosquito Survey in Tizi-Ouz y in Tizi-Ouzou (Algeria Nor ou (Algeria Northern): Updated thern): Updated Inventory with New Reports - Soumeya Chahed; Hania Belkacem; Lynda Boukhari; Karima Brahmi (Journal of Bioresource Management, 2022)
Mosquitoes play an important role in public health, they are responsible for the transmission of pathogens that cause infectious diseases to both humans and animals. The study of this fauna biodiversity is necessary to determine the vector species of diseases. Our inventory of mosquitoes in Tizi-Ouzou province has been updated in this study, it was carried out from April to September, 2021 at 43 breeding sites, spread over ten different communes. The inventory was based on the sampling of larvae and the capture of adults on human bait. The identification of Culicidae inventoried revealed the presence of 14 species belonging to five genera and two subfamilies. We report the first citation of four species for this region, these are Culex (Culex) laticinctus Edwards, 1913, Culex (Culex) mimeticus Noe, 1899, Aedes (Ochlerotatus) berlandi (Seguy, 1921) and Coquillettidia (Coquillettidia) richiardii (Ficalbi, 1889). The genus Coquillettidia was cited for the first time in Tizi-Ouzou. The data of this study was exploited by the ecological indices in order to have the relative abundance and the frequency of occurrence.